(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research aims to show or present The Impact of COVID-19 on small business owners in Barangay Sta. Monica, Novaliches Quezon City Year 2021 - 2022. The researchers used a quantitative approach emphasizing objective measurements and statistical, mathematical, or numerical data analysis obtained through polls, questionnaires, and surveys. This study aims to determine the perception of Barangay Sta. Monica, Novaliches Quezon City of having the Impact of Covid 19 Pandemic on small business owner. The most important in his study is to identify the impact of this pandemic on business owners.